THE QUINTESSENCE OF MULK RAJ ANAND’S NOTION OF FERVENT SOCIALISM IN THE INDIAN ETHOS - Jose, Bijesh V. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mulk Raj Anand, the most prolific writer and the pioneer of Indian English fiction in the twentieth century, had an enlarged and magnanimous vision of the whole human race. When Anand wrote his first four novels in the 1930’s, he responded to the world-wide tendency of using a sociological approach in literature. Anand was proved to be a product of a particular phase in the evolution of twentieth century ideas. Mulk Raj Anand is a committed artist with a philosophical paradigm and moral and poetic vision of life. The image of India is the focal point of his creative imagination. Mulk Raj Anand’s humanism consists in a system of thought in which humanitarian interests, values and dignity are held foremost. It implies commitment to the concerns of humanity. It is an attitude that centres on the activities of man rather than on the supernatural world. His humanism makes him to use his art for the services of humanity. Anand was filled with a purpose – to emphasise the quandary of the poor, suffering masses of India. Only he would dare to make the lowest of the lowly his hero for the first time in the history of Indian English fiction – Bakha, in the Untouchable. He would repel against any form of compulsion or fascist moves which angst his countrymen. This Paper examines the quintessence of Mulk Raj Anand’s notion of fervent socialism in the Indian ethos.